الاحكام الفقھیة للمولود في الاسبوع الاول (Journal of the College of Education for Women, 2019)
Islam had come to urge for justice, to call for the freedom of the human and toassert his dignity. Islamic education focused on the perfect growth of theindividual, presence of the human and his future as well. The Islam also attended ineducation of the child raising him with respect all aspects of life. All of these thingshad made the Islamic education as an extensive and balanced. There is no wonderto consider Islam as the main source of legislation to attain its definitive aim whichis to establish a rational sober human worships God and educates the earth wherehe settle down and make use of all its blessings due to God's legislation. (Shari 'a)If Islam takes care of raising upbringing a child since his first moments in lifetill he gets married, such interest get intensified gradually. The research tackles indetail Islam's interest in raising a child during the first week after birth. Some ofthese moralities and legislation that are followed with an infant are:1- Calling the prayer in his right ear and perform virtual prayer in his left eardirectly after birth.2- Seasoning the infant with dates.3- Giving the infant one of good names.4- Scarifying for him.5- Cutting his hair and giving a benefaction that equals the cut hair.6- Circumcising the infant.